ISU MUTAKHIR DALAM BIDANG KIMIA DAN BIOMONITORING UNTUK KESELAMATAN DAN KESEHATAN KERJA (K3) - Qandiyas Sadin, Syesar; Susilawati, Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
This journal discusses the latest issues in the field of chemistry and biomonitoring related to occupational safety and health (K3). The aim of this journal is to provide a comprehensive and up-to-date insight into the latest developments in this field as well as provide solutions and recommendations to address emerging issues. The approach taken in this journal includes a literature review of the latest research and findings, as well as a critical analysis of issues related to the safety and health of workers in work environments exposed to chemical substances.